2014
DOI: 10.1097/mnm.0000000000000161
|View full text |Cite
|
Sign up to set email alerts
|

The importance of a supportive environment in clinical audit

Abstract: The study makes use of a unique data set and to the best of our knowledge is one of the first studies to document how the dissemination of doctors' performance data positively influences engagement with clinical audit in England. In addition, the study also shows how, contrary to some studies in the literature, clinical audit can reduce professional anxiety by providing a validation of professional competence. The study supports the premise that clinical audit will be fully embraced by doctors only if they are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…61 The structure of the current audit ensured adequate time and resources were available for the working group and other key stakeholders, in an environment supporting a learning culture. 64,65 The results of the current audit suggest that dystocia case management broadly improved through each audit phase, including a significant increase in the use and recording of neonatal monitoring via fetal heart rate assessment during ultrasonography. This is encouraging, as diagnostic imaging is reported as a critical tool for successful management of canine dystocia.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…61 The structure of the current audit ensured adequate time and resources were available for the working group and other key stakeholders, in an environment supporting a learning culture. 64,65 The results of the current audit suggest that dystocia case management broadly improved through each audit phase, including a significant increase in the use and recording of neonatal monitoring via fetal heart rate assessment during ultrasonography. This is encouraging, as diagnostic imaging is reported as a critical tool for successful management of canine dystocia.…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, it has been reported that change in practice is positively influenced when the professional and organisational culture supports QI 61 . The structure of the current audit ensured adequate time and resources were available for the working group and other key stakeholders, in an environment supporting a learning culture 64,65 …”
Section: Discussionmentioning
confidence: 99%
“…The participants' report quality for each case was independently assessed by one of two dual-certified radiology and nuclear medicine physicians with >15 years of experience using a standard 5-point audit score used in routine clinical practice (18,19) (Table 3). Reports generated in both arms of the study (with and without AI) by a participant radiologist for a specific PET/CT case were scored for quality by the same assessor.…”
Section: Report Qualitymentioning
confidence: 99%
“…Furthermore, these audits are opportunities to educate and train healthcare professionals. 4,5 This study emphasises the importance of clinical audits as a valuable part of practice in the developed world. Most of our undergraduate students need more knowledge and understanding about audits and the audit cycle.…”
Section: Introductionmentioning
confidence: 99%